العلاقات الاجتماعية وتعزيز الاندماج الاجتماعي للتجار المزابيين في المجتمع المحلي (1962-2018) دراسة ميدانية بمدن الغرب الجزائري - لطروش, بلقاسم (جامعة وهران 2, 2025)
ملخص: تعالج هذه الأطروحة العلاقة بين العلاقات الاجتماعية التي ينسجها التاجر المزابي في منطقة الغرب الجزائري واندماجه في المجتمع المحلّي لكل مدينة، حيث يمثل النشاط التجاري مجالا اجتماعيا غنيا بالعلاقات الاجتماعية والمعاملات التجارية في المحيط الحضري الذي يحوز على سوق استهلاكية كبيرة. لقياس هذه العلاقة بين المتغيرين اعتمدنا على المزج بين المنهج الكمي والكيفي؛ من أجل الإحاطة الواسعة قدر الإمكان لمسار هجرة الجماعة المزابية من وادي ميزاب إلى مدن الغرب الجزائري وواقع العلاقة بين التاجر المزابي والرجل المحلّي، معتمدين في ذلك على الاستمارة والمقابلة لجمع المعلومات اللازمة لقياس هذه العلاقة، وكانت من أهم النتائج المتحصل عليها وجود علاقات صداقة وجيرة قوية بين الطرفين في المدينة، كما يوجد علاقة مصاهرة بين التاجر والمحلّي وأكثر من هذا مشاركة المزابي في نشاطات المجتمع المحلّي في منطقة الغرب الجزائري. Résumé: La thèse traite la relation entre les relations sociales que le commerçant Mozabite les ai tissé dans la région de l’Ouest algérien et son intégration dans la communauté locale de chaque ville, où l’activité commerciale est un espace social riche en relations sociales et transactions commerciales dans l’océan urbain qui détient un grand marché de consommation. Cette relation entre les deux variables nécessite une mesure scientifique, ou nous nous sommes appuyés sur une combinaison d’approches quantitatives et qualitatives ; Afin de capturer le plus largement possible le parcours migratoire de la communauté Mozabite de la vallée de M’Zab aux villes de l’Ouest algérien et la réalité de la relation entre le commerçant et l’individu local. En basant sur la technique du formulaire et l’entretien pour avoir des informations nécessaires afin examiner cette relation, l’un des résultats les plus importants obtenus a été l’existence de relations amicales et de bon voisinage entre les deux parties dans la ville. Il y a aussi un rapport entre le commerçant et le local où la participation du commerçant aux activités de la société locale dans la région algérienne occidentale est fort.
Keywords: Commerce -- Mzab; Emigration -- Mzab -- Algérie

Visibilité et invisibilité dans l’espace public algérien : les stratégies des femmes mozabites pour se voiler au M’Zab et à El-Eulma - Gueliane, Nora; Abderrezek, Kaouther (Cahiers d'études africaines, 2024)
Cet article, centré sur l’usage du corps et le style vestimentaire, interroge ce que ceux-ci nous disent du respect des normes de genre et de la capacité, ou de la volonté, de transiger avec celles-ci ou de se les réapproprier à son avantage. Il se fonde sur une étude portant sur des femmes mozabites vivant dans leur territoire d’origine (le M’Zab), et dans un territoire d’accueil, la ville d’El-Eulma (Setif). La comparaison entre ces deux espaces permet d’éclairer et de mesurer le décalage entre les usages du corps et du vêtement selon le poids démographique et la force des liens de sociabilité. Le port du voile aḥouli, accessoire qui, au M’Zab, sert à l’invisibilité des femmes mozabites, se révèle accroître leur visibilité ailleurs, de sorte que celles-ci peuvent vouloir l’ôter pour gagner en invisibilité.
Keywords: Emigration -- Mzab -- Algérie; Moeurs et coutumes -- Mzab

Preserving Mzabi Dialect Vitality: The Case Study of Mozabite Merchants in the City of Constantine - Benlahrache, Wafa Safinez (Revue des Sciences Humaines, 2024)
The Mozabite people constitute a well-known Berber ethnic group who have lived in Algeria for centuries. The Mzabi dialect is their native tongue and Arabic is spoken by many as a second language. Therefore, this paper is an attempt to look into certain parameters surrounding this case of bilingualism. It aims more precisely to check whether or not constant contact with dialectal Arabic in particular might have any effect on the use and maintenance of the Mzabi dialect and tries to figure out the underlying reasons behind it. Accordingly, data are mainly collected using structured interviews with a sample that consists of twenty-five Mozabite merchants in the city of Constantine. The investigation generated comparable results and reveals that Mozabites intentionally speak both dialects separately, depending on context and purpose. It also demonstrates that Mzabi resists change and attrition due to its speakers’ deep sense of belonging to a highly conservative community.
Keywords: Emigration -- Mzab -- Algérie; Linguistique -- Mzab

شهادة عائد من سجن كايان بن قاسم, بائع الفحم - بكير, أبي إسماعيل (Naqd, 2024)
Keywords: Biographies -- Mzab -- 20e siècle; Emigration -- Mzab -- Algérie; Mouvement national -- Mzab

Migration, mémoire et tourisme, l'exemple des Mozabites - Abderrezek, Kaouther (Le tourisme de mémoire: un atout pour les collectivités territoriales ?, 2015)
Keywords: Emigration -- Mzab -- Algérie

مفهوم العمل وعلاقته بالتغير الاجتماعي دراسة ميدانية للمزابيين العاملين بالعاصمة - حاج سعيد, إبراهيم (جامعة الجزائر 2, 2011)
Keywords: Emigration -- Mzab -- Algérie

The Road to Ghardaïa: Investigating a Community Deep in the Sahara Leads to the Study of Global History - Holsinger, Donald C. (Mennonites and Post-Colonial African Studies, 2021)
Keywords: Emigration -- Mzab -- Algérie

M. Roger Léonard en visite au M’zab (La vigie marocaine, 1952)
ALGER. 21 avril (P.P ). — A l’occasion des fêtes du Chouffane. M Roger Léonard, gouverneur général de l’Algérie, vient de passer deux Jours au Mzab, Dans un discours prononcé â Beni-Inchen. Il a déclaré qu'il estimait possible d’apporter une solution au problème de l'eau, particulièrement dans le domaine de l’irrigation, et souligne l’Importance que représente pour l'équilibre économique de l’Algérie l’exode périodique des populations mozabltes vers le Nord.
Keywords: Emigration -- Mzab -- Algérie

Les bains d'Alger durant la période ottomane, XVIe-XIXe siècles - Cherif-Seffadj, Nabila (Presses de l'Université Paris-Sorbonne, 2008)
Keywords: Emigration -- Mzab -- Algérie

Dilemmas of desert survival in an age of imperialism: Mizabi merchants in Algeria from 1830 to 1850 - Holsinger, Donald C. (The Journal of North African Studies, 2017)
Algiers under Ottoman rule contained an elaborate system of barrani (literally ‘foreigner’) corporations whose members were united by occupational specialisation and ethnic or racial identity. These corporations managed their affairs semi-autonomously under the leadership of one or several of their members while remaining vulnerable to political authorities who could threaten to withdraw occupational concessions. By the early nineteenth century, the Mizabi corporation was among the most prominent at Algiers, enjoying a quasi-monopoly over commercial enterprises such as flour mills, butcher shops, and public baths. The 1830 French conquest of Algiers confronted Mizabi merchants with an excruciating dilemma. The stakes were enormous for these Muslim sectarians who (1) played a central role in the survival of their Saharan home community, (2) served as key links in Algerian communication networks, and (3) made vital economic contributions to coastal cities. The Saharan community’s political submission to an alien power seemed unthinkable; starvation resulting from French threats to cut off caravan links to the Mizab was equally unthinkable. This study examines the background and impact of the 1838 and 1850 decrees reorganising the barrani corporations of French-controlled Algeria. Buffeted and torn by the dilemmas of political accommodation and Saharan survival, Mizabi merchants demonstrated remarkable resilience during a turbulent and transitional era.
Keywords: Emigration -- Mzab -- Algérie

نمط القيادة في المجتمع الميزابي: دراسة ميدنية لتجار مدينة عنابة - طوراوي, منيرة (جامعة ناجي مختار, 2008)
Keywords: Emigration -- Mzab -- Algérie

الدور الاقتصادي لجماعة بني مزاب بمدينة الجزائر خلال العهد العثماني (١٥١٨-١٨٣٠م/٩٢٤-١٢٤٥هـ) - بوسعدة, يوسف (جامعة الشييد حمو لخضر, 2016)
Keywords: Emigration -- Mzab -- Algérie

تركيبة مجتمع مدينة الجزائر خلال العهد العثماني (1519-1830) - جماعة بني ميزاب أنموذجا - - الزرويل, صالح (المركز الجامعي بغرداية, 2009)
Keywords: Emigration -- Mzab -- Algérie; Mzab -- Histoire -- 1510-1830

Migration, Commerce and Community: the Mīzābīs in Nineteenth-Century Algeria - Holsinger, Donald C. (Northwestern University, 1979)
Keywords: Emigration -- Mzab -- Algérie

Les jurisdictions compétentes en matière de litiges intéressant les mozabites résidants hors du Mzab - Rinn, Louis (Revue algérienne, tunisienne et marocaine de législation et de jurisprudence, 1887)
Keywords: Emigration -- Mzab -- Algérie

Muslim Responses to French Imperialism: An Algerian Saharan Case Study - Holsinger, Donald C. (The International Journal of African Historical Studies, 1986)
The political events that preceded French occupation of Mīzāb, based mainly on French archivial materials. The awkward position of the Mīzābīs between French superior military power, which could easily destroy their trading activities in the North if they would not submit to French demands, and the threat of attaques on them by rebels in the South and their nomadic supporters if they would openly submit to the French and support them. This dilemma led to fierce internal strife in Mīzāb.
Keywords: Emigration -- Mzab -- Algérie

Migration, Commerce and Community: the Mīzābīs in Eighteenth-and Nineteenth-Century Algeria - Holsinger, Donald C. (The Journal of African History, 1980)
The Mīzāb is an Ibādī community consisting of seven cities clustered in an arid rocky region 350 miles south of Algiers. Having established these settlements nearly a millennium ago, the Mīzābīs, as the inhabitants came to be known, struggled against formidable environmental odds and managed not only to survive but to prosper. By the sixteenth century the Mīzāb had become an important northern Saharan market. During the following centuries, the Maghrib witnessed a remarkable movement of Mīzābī men to coastal cities where they attained prominence in a variety of professions while leaving their roots firmly implanted within their distant oasis community. Following a brief historical background to settlement in the Mīzāb, this article sketches the ecological constraints of an urban community in a region virtually devoid of resources. It then traces the history of the commercial dispersion to the North during the eighteenth and nineteenth centuries and discusses the probable causes of emigration. The Mīzābīs were forced by environmental constraints to seek outside sources of support. Their rise to prominence in the Regency of Algiers may have been related to declining Saharan commerce and new commercial opportunities in the North. The organization and function of Mīzābī corporations in Algiers and other northern cities are described. Finally, this article relates an Ibāçī reform ethic to Mīzābī commercial success and concludes with some reflections on religious ideology and environmental demands as contributing factors to the long-term Mīzābī role in commerce.
Keywords: Emigration -- Mzab -- Algérie

Trade routes of the Algerian Sahara in the nineteenth century - Holsinger, Donald C. (Revue de l'Occident musulman et de la Méditerranée, 1980)
A study of the impact of French imperialism on northern Saharan trade. Mīzāb’s important role in this trade
Keywords: Emigration -- Mzab -- Algérie

Quelques documents sur la corporation des Mozabites d’Alger dans les premiers temps de la conquête (1830-1838) - Lespès, René (Revue Africaine, 1925)
A critical study with reference to a letter of Mīzābīs in Algiers to the commander of the French occupying forces intended to keep the priviliges they had acquired under the Turks.
Keywords: Emigration -- Mzab -- Algérie

Thalāthu Rasā’il Makhṭūṭa ḥawla al-Ibāḍiyya al-Mīzābiyyīn bi’l-Jazā’ir fī ‘l-ʿAhd al-ʿUthmānī - Baḥḥāz, Ibrāhīm (Revue d'Histoire Maghrébine, 1998)
The Ottoman period in Algeria was from 1515-1830. These three letters are from the private library of Muḥ. al-Ḥājj Saʿīd b. Ayyūb in Ghardaïa, Mīzāb. The first letter (Dhū ‘l-Qaʿda 1206/1792) contains a complaint from the Mīzābīs to the Dāy Bābā Ḥasan (1791-1798) about the intention of Ṣāliḥ Bāy, Bāy of Constantine (1771-1792), to subdue the Mīzābīs and their families, to lead their women and children into captivity, and subsequently to exterminate them, probably for no other reason then their belonging to the Ibāḍī Madhhab. The second letter (Muḥarram 1207/Aug. 1792) is a letter of thanks for the Dāy’s help. The third one (end of Ṣafar 1207/1792), to al-Ḥājj ʿAlī b. ʿAbd al-Laṭīf, Siḥr of the Dāy and their mediator with the Dāy, “expresses the acknowledgment of what is beautiful by its writers”; it contains the aforementioned complaint and the Mīzābīs’ gratitude.
Keywords: Emigration -- Mzab -- Algérie

Islam and state expansion in Algeria: nineteenth-century Saharan frontiers - Holsinger, Donald C. (Islamism and secularism in North Africa, 1994)
Keywords: Emigration -- Mzab -- Algérie

امتيازات جماعة بني مزاب في مدينة الجزائر العثمانية - ناصر, بالحاج بن باحمد (المنهاج, 2015)
Keywords: Emigration -- Mzab -- Algérie; Mzab -- Histoire -- 1510-1830

Migration interne et classes moyennes en Algérie : le cas des Mozabites - Holsinger, Donald C. (Les Classes moyennes au Maghreb: ouvrage collectif, 1980)
Keywords: Emigration -- Mzab -- Algérie

Une lettre des Mozabites d'Alger en 1848 - Emerit, Marcel (Bulletin de Liaison Saharienne, 1953)
Keywords: Emigration -- Mzab -- Algérie

Réseau migratoire et intégration des nouveaux migrants : exemple des communautés mozabites d'El Eulma (Algérie) et de Marseille ( France) - Abderrezek, Kaouther; Fournier, Mauricette (Session « Migration : réseaux d’acteurs et accueil de nouvelles populations », 2016)
Cet article s’intéresse aux conditions d’accueil des migrants et à leurs modèles d’intégration dans leurs nouveaux territoires d’installation à partir de l’analyse des réseaux migratoires, des initiatives conduites par les acteurs en dehors de tout cadre institutionnel. Pour étudier le phénomène, notre attention s’est portée sur une communauté ethno-linguistique et religieuse particulière, les Mozabites, observée dans deux contextes migratoires distincts : El Eulma, une ville du nord algérien et Marseille, métropole du sud de la France. L'étude de cette minorité a permis de mesurer le rôle que peut jouer l’identité d'un groupe, sa cohésion sociale et le réseau migratoire qu'il a établi, dans le développement de l’accueil des nouveaux migrants : comment ces caractéristiques se manifestent-elles pour favoriser l’intégration des nouveaux arrivants dans les territoires d'installation. Après une brève présentation de la communauté mozabite et ses spécificités culturelles, sont analysées les initiatives développées par ses membres pour favoriser l’accueil et l’intégration des nouveaux arrivants dans les deux villes d’accueils.
Keywords: Emigration -- Mzab -- Algérie

L'insertion des Mozabites d'Algérie dans les territoires d'accueil - Gueliane, Nora (Sociétés Plurielles, 2019)
Keywords: Emigration -- Mzab -- Algérie

L'émigration temporaire des M'zabites dans les villes du Tell algérien - Vigourous, L. (La France méditerranéenne et africaine, 1939)
Keywords: Emigration -- Mzab -- Algérie

L'émigration mozabites dans les villes du Tell algérien - Vigourous, L. (Travaux de l'Institut de Recherches Sahariennes, 1945)
Keywords: Emigration -- Mzab -- Algérie

Effects of the transition from the Turkish and the French Regime in Algiers : the case of the Mzabi Talaba (Tolba) - Hoexter, Miriam (Asian and African Studies, 1983)
The purpose of this paper is to find out how and in what ways French policy, during and after the corporative (Barrāniyya) phase (until 1868), affected the traditional position and functions of the Mīzābī Ṭalaba in Algiers. I.a. based on documents in the French National Archives in Paris and in Les Archives du Gouvernement Général de l’Algérie, Aix-en-Provence.
Keywords: Emigration -- Mzab -- Algérie

L'émigration temporaire des mozabites dans les villes du tell Algérien - Vigourous, L. (Centre des hautes études sur l'Afrique et l'Asie moderne, 1941)
Keywords: Emigration -- Mzab -- Algérie

Implantation des Mozabites dans l'Algérois entre les deux guerres - Bendrissou, Salah (Université de Paris 8, 2000)
Tout en maintenant leur intégrité communautaire, les Mozabites durent s'expatrier se livrant au commerce, comme moyen principal pour survivre. Ces activités commerciales ont de plus contribué à individualiser ce groupe social. L’émigration mozabite vers le Nord algérien aurait commencé dès le début du XIVe siècle. Peu à peu, l'implantation mozabite s'est diffusée dans les centres urbains du Nord. Le présent travail s'inscrit à la fois dans un cadre historique et social. Fait d'origine économique, l'émigration produit en premier lieu des résultats économiques. Elle entraîne des conséquences sociales importantes. Enfin, comme tout fait humain et économique, elle conduit parfois à des situations juridiques singulières. Le comportement économique de la société mozabite, l'aspect et les traits caractéristiques de son émigration, les activités commerciales, sociales, culturelles et politiques menées dans l'Algérois par ce groupe sont les éléments dominants de cette étude.
Keywords: Emigration -- Mzab -- Algérie

Migrations, territorialités, dynamiques interculturelles: L'exemple de la minorité mozabite - Abderrezek, Kaouther (Université Clermont Auvergne, 2017)
À l’heure où la mobilité est accrue et les valeurs culturelles se dirigent de plus en plus vers l’unification, il nous a paru important d’observer les migrations des groupes diasporiques à fortes valeurs identitaires et d’analyser leurs territorialités et leurs dynamiques interculturelles. Ce travail ambitionne donc d’amorcer une étude géographique du phénomène migratoire diasporique. Il porte le regard sur l’analyse de l’espace migratoire qui se forme entre le lieu d’origine du groupe minoritaire et ses pôles d’installation avec un exemple précis sur la minorité ethnolinguistique et religieuse des Mozabites algériens qui migrent et s’approprient différents pôles dans le contexte interne et international. Le choix d’analyser plusieurs pôles d’installation (El-Eulma en Algérie, Marseille et Lille en France) et de mettre en rapport la migration interne et la migration internationale de ce groupe, a permis d’évaluer l’influence des différents facteurs sur la conception des phénomènes migratoires diasporiques. Il a aussi éclairé sur la manière dont l’appartenance identitaire est une variable que le groupe diasporique sollicite fortement pour former son espace et son système migratoire At a time when mobility is increasing and cultural values are moving more and more towards unification, it was important to observe the migration of diasporic groups with strong identity values and to analyze their territorialities and intercultural dynamics. This work aims to initiate a geographical study of the diasporic migratory phenomenon. It is concerned with the analysis of the migratory space between the original place of the minority group and its poles of settlement with the specific example of the ethnolinguistic and religious minority of the Algerian Mozabites who migrate and appropriate different clusters in the internal and international context. The choice of analyzing several installation clusters (El-Eulma in Algeria, Marseille and Lille in France) and to compare the internal migration with the international migration of this group, made it possible to evaluate the influence of the different factors on the design of diasporic migratory phenomena. It also enlightened on how identity belonging is a variable solicited by the diasporic group to form its space and its migratory system
Keywords: Emigration -- Mzab -- Algérie